Enhanced Recovery Pathway Reduces Hospital Stay and Opioid Use in Microsurgical Breast Reconstruction: A Single-Center, Private Practice Experience. Issue 1 (2nd May 2022) - Ochoa, Oscar; Rajan, Meenakshi; Garza, Ramon; Chrysopoulo, Minas; Pisano, Steven; Ledoux, Peter; Arishita, Gary; Michalek, Joel; Nastala, Chet
Abstract : Background: This study aimed to determine benefits of the Enhanced Recovery After Surgery (ERAS) pathway implementation in free flap breast reconstruction related to postoperative narcotic use and health care resource utilization. Methods: A retrospective analysis of consecutive patients undergoing deep inferior epigastric perforator flap breast reconstruction from November of 2015 to April of 2018 was performed before and after implementation of the ERAS protocol. Results: Four hundred nine patients met inclusion criteria. The pre-ERAS group comprised 205 patients, and 204 patients were managed through the ERAS pathway. Mean age, laterality, timing of reconstruction, and number of previous abdominal surgical procedures were similar ( p > 0.05) between groups. Mean operative time between both groups (450.1 ± 92.7 minutes versus 440.7 ± 93.5 minutes) and complications were similar ( p > 0.05). Mean intraoperative (58.9 ± 32.5 versus 31.7 ± 23.4) and postoperative (129.5 ± 80.1 versus 90 ± 93.9) morphine milligram equivalents used were significantly ( p < 0.001) higher in the pre-ERAS group. Mean length of stay was significantly ( p < 0.001) longer in the pre-ERAS group (4.5 ± 0.8 days versus 3.2 ± 0.6 days). Bivariate linear regression analysis demonstrated that operative time was positively associated with total narcotic requirements ( p < 0.001) and length of stay ( p < 0.001). Conclusions: ERAS pathways in microsurgical breast reconstruction promote reduction in intraoperative and postoperative narcotic utilization with concomitant decrease in hospital length of stay. In this study, patients managed through ERAS pathways required 46 percent less intraoperative and 31 percent less postoperative narcotics and had a 29 percent reduction in hospital length of stay. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.